Implications of the Decentralization Policy on Poverty Reduction in Indonesia - Marlan Hutahaean (Indonesian Association for Public Administration, 2020)
This paper aims to analyze the implications of decentralization policies that are linked to poverty reduction in Indonesia. The focus of the study is the decentralization policy as regulated in Law No. 22/1999, which was amended twice through Law No. 32/2004 and Law No. 23/ 2014 concerning local government. In addition, it also discussed Law No. 25/1999 concerning financial relations in the central-regional government. Using qualitative methods with a policy/program analysis approach and secondary data, this study found that decentralization policies do not link directly to poverty reduction. Out of 34 provincial regions, only 8 provincial regions have achieved a human development index (HDI) above the national average, while having a poverty rate below the national average. In contrast, there are 13 provincial regions that reached HDI below the national average and at the same time have poverty levels above the national average. Based on these findings, this study recommends, first, that local governments evaluate and direct various programs that lead to HDI improvement and poverty reduction. Second, that they synchronize poverty reduction programs in the regions with the same programs from the central government and international programs in the regions.